Avaliação na ótica do beneficiário quanto a efetividade do Programa de Capacitação Empresarial no âmbito do PRODETUR / NE II na Costa do Descobrimento - Bahia. - Santos, Salomão Lelis Moraes dos (2014)
This study contemplates an evaluation ex post of the Programa de Capacitação Empresarial in the context of the PRODETUR/NE II of the Polo Costa do Descobrimento in the state of the Bahia. In treating the difficulty as an evaluation of public projects, mainly those of hallmark economical-partner, of a consensus having been as for the concepts, techniques and methodologies of his application, they translate in conflicts and frustration, what for his time, becomes more difficult his realization of systematic form. The objective of this work is to value the Program developed by the Government of the State of the Bahia in partnership with the Banco do Nordeste do Brasil, the Inter-American Bank of Development and the Ministério do Turismo, which main objective was it of promoting the business development, through the train and capacitate of the businessmen and Manager location, connected with the continuation of the tourism, main commercial activity of the Pole, which for his time, takes the quality of the installment of service as a primordial element for the development and prosperity of the business. For so much bibliographical inquiry was carried out on basis of the theoretical referential systems relative to the PRODETUR/NE II, the Programa de Capacitação Empresarial of the Polo Costa do Descobrimento and the Evaluation of Public Policies. Field work happened still, through the questionnaires application near the target public, boarding three kinds established by the program, with the intention of checking the perception of these actors as for the reached benefits, as well as checking the results reached by the execution of the program, and in this form to be able to understand the process for which the program managed or not to reach his objectives. The search results of the field work give support to evaluation of the program, making possible to point to positive points and some weaknesses of his execution. To the end the final considerations are presented and listed suggestions to be observed in future programs, with the purpose of promoting improvements that provide to reach the effectiveness of the public policies turned to actions of capacitate business.